Health-seeking behaviour and delayed presentation of oral cancer patients in a developing country: A qualitative study based on the self-regulatory model - Azhar, Nurizyani; Doss, Jennifer Geraldine (West Asia Organization for Cancer Prevention, 2018)
Background: The aim of this study was to explore reasons for delayed health-seeking for late stage oral cancer patients. Methods: Semi-structured in-depth interviews were conducted with 35 oral cancer patients with TNM stage III to IV disease, who were treated at six tertiary regional centres managing oral cancer throughout Malaysia. Interviews were audio-recorded, transcribed verbatim, coded using NVivo (version 10.0) qualitative software and analysed using framework analysis. Results: Participants interpreted their early symptoms as a minor condition and did not consider it as requiring immediate attention. Four types of coping strategies causing delayed help-seeking emerged: 1) self-remedy 2) self-medication 3) seeking traditional healers and 4) consulting general medical practitioners (GPs) instead of dentists. Socio-economic factors, cultural beliefs and religious practices have some influence on diagnostic delay. Conclusion: Low levels of public knowledge and awareness regarding early signs and symptoms of oral cancer as well as GPs' misdiagnosis of early lesions results in delayed diagnosis.